Analisis Keefektifan Kalimat dalam Teks Deskripsi Bertema Keberagaman Alam Indonesia pada Laman Good News From Indonesia Edisi Januari 2025 sebagai Kelayakan Teks Membaca - Dhuha Balqis Syahida Adira; Melani Khoirun Nisa; Haufa Dilla; Indah Berlianne Sulistyawati; Najma Sofi Yuliana; Asep Purwo Yudi Utomo; Eko Ahmad Riyanto; Molas Warsi Nugraheni (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research analyses the effectiveness of descriptive text sentences on the January 2025 edition of Good News From Indonesia as a reading text feasibility. This research is motivated by the writer's analysis of sentences in descriptive texts that do not follow Indonesian language rules. This study aims to review the effectiveness of sentences in four description texts published on the Good News From Indonesia page, which are examined based on cohesion and coherence, word inefficiency, word inflexibility, and spelling errors, to produce more effective sentences, following Indonesian language rules. The method used in this research is a descriptive and theoretical approach using syntax to analyse the effectiveness of sentences. The analysis results in the 4 Good News From Indonesia description texts show several ineffective sentences, including word inefficiency, word inflexibility, spelling errors, and cohesion and coherence between sentences. With this research in analysing sentence effectiveness, it is hoped that it can increase readers' knowledge and insight into understanding the importance of effective sentences in descriptive texts.